Investigating the impact of aging and hyperlipidaemia on metformin cardioprotection against carfilzomib-induced cardiotoxicity in vivo. (25th November 2020) - Psarrakou, G; Chatzistefanou, M; Efentakis, P; Varela, A; Papanagnou, E.D; Nikolaou, P.E; Tsoumani, M; Davos, C.H; Kastritis, E; Trougakos, I.P; Dimopoulos, M.A; Terpos, E; et al.
Abstract: Background: Carfilzomib (Cfz) is an irreversible proteasome inhibitor, indicated for the treatment of Multiple Myeloma (MM); however, is associated with cardiotoxicity in humans. Metformin (Met) has been suggested as a prophylactic therapy against Cfz-induced cardiotoxicity in mice. Purpose: Considering that MM is an elderly disease, manifested in presence of cardiovascular comorbidities, we investigated the cardioprotective effect of Met against Cfz-cardiomyopathy on the age- or hyperlipidaemia-burdened myocardium in vivo. Methods: Aging model: Male C57BL/6 mice, 15-month old, were randomized into: 1. Control (N/S 0.9%), 2. Met (140 mg/kg, po), 3. Cfz (8mg/kg, ip) and 4. Cfz+Met (8 and 140 mg/kg respectively) (n=5–7/group). Hyperlipidaemic model: ApoE−/− male mice, 20-weeks old were randomized into: 1. Control (N/S 0.9%), 2. Met (140 mg/kg, po), 3. Cfz (8mg/kg, ip) and 4. Cfz+Met (8 and 140 mg/kg respectively) (n=6/group). Cfz was administered every 48 hours and Met every 24 hours for 6 days. At baseline and at the end of treatments mice underwent echocardiography. Proteasomal activity and molecular signaling mechanisms were assessed in myocardial tissue and in peripheral blood mononuclear cells (PBMCs). Results: Aging model: Proteasome activity was significantly reduced in myocardial tissue of aged vs young mice (P<0.05). Cfz-treated mice showed an additional decrease in proteasomal activity compared to Control (P<0.05) and Met (P<0.01) groups, in heart and PBMCs. A significant fractional shortening (FS%) reduction was observed in Cfz group vs controls at day 6 (29.90±1.7 vs 37.60±0.2, respectively, P<0.05) while Met in both Met and Cfz+Met groups maintained FS% vs controls (34.88±1.6, 33.20±0.6 vs 37.60±0.2, respectively, P=NS). By investigating molecular signaling pathways involved in cardioprotection, we observed that Cfz led to a decrease of Akt and AMPKα phosphorylation (P<0.05 vs Control), whereas Cfz+Met co-administration restored Akt and AMPKα phosphorylation and upregulated t-eNOS and t-Akt (P<0.05 vs Control). Hyperlipidaemic model: In ApoE−/− mice, no significant reduction of myocardial proteasomal activity was observed, whilst PBMCs proteasomal activity was decreased compared to controls (P<0.05). Cfz treated ApoE−/− mice exhibited a reduction of myocardial (P<0.01 in Cfz and P<0.001 in Cfz+Met) and PBMCs' proteasome activity (P<0.001) vs controls. Interestingly, Cfz, Met as well as the combination led to a decrease in FS% versus controls (44.00±1.2, 42.33±0.92, 42.33±1.0 vs 47.50±0.72 respectively, P<0.05). Conclusions: Our results demonstrate that Met retains its prophylactic potency against Cfz-induced cardiotoxicity in aged mice and activates cardioprotective signaling molecules. In the ApoE−/− mice, Met failed to exert cardioprotection against Cfz induced cardiomyopathy. Therefore, the monitoring of the cardiovascular burden seems to be of outmost importance in managing Cfz cardiac adverse effects. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Amgen